Caries Risk Assessment and Prevention - Ratnawati Hendari (Jurnal LINK, 2012)
Oral health has improved, but the prevalence of dental caries, especially in children remains a significant clinical problem. In order to reach the target teeth healthy in 2010 according to WHO standards, we need a preventive measure. This paper will discuss the identification and assessment of risk factors for early caries, caries prevention based caries risk factors. Whole precautions either primary prevention, secondary or tertiary should be based on clinical and radiographic examination. Early detection and caries risk assessment provides an opportunity for the dentist to perform preventive dental disease before it is evident. The conclusion of this paper is that the caries risk assessment is a method to identify the risk of caries. Precautions should see the main cause of dental caries indicator.